PERANCANGAN SISTEM INFORMASI AKADEMIK SMA PERTIWI 2 PADANG MENGGUNAKAN BAHASA PEMOGRAMAN PHP DAN MYSQL - Angga Putra Juledi (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2021)
Technology is growing rapidly in the midst of society today, making people competing to master and implement it in everyday life such as students. Students are entitled to master the current technology activity, not just to earn income or mere skill, but science is currently used for things that lead to advancements and skills that are useful for the future. Similarly, the teachers and students, for the ease and smoothness of teaching and learning process, it takes a simple system application and can help the learning process in teaching and learning activities. With the development of technology in the world of computerization and application of Academic Information system applications in SMA Pertiwi 2 Padang can help manage academic data effectively and efficiently because it can be accessed online and academic data stored electronically.